Identification of CSPG4 as a promising target for translational combinatorial approaches in osteosarcoma. (June 2019) - Riccardo, Federica; Tarone, Lidia; Iussich, Selina; Giacobino, Davide; Arigoni, Maddalena; Sammartano, Federica; Morello, Emanuela; Martano, Marina; Gattino, Francesca; Maria, Raffaella De; Ferrone, Soldano; Buracco, Paolo; et al.
Background: Osteosarcoma (OSA) is a highly metastatic pediatric bone tumor. Adjuvant chemotherapy and surgical resection represent standard treatments; however, the prognosis is still poor. Effective strategies are urgently needed. Chondroitin sulfate proteoglycan (CSPG)4 is a transmembrane proteoglycan with a low expression in normal tissues but high expression in several solid tumors, where it plays a central tumorigenic role. Therefore, it represents a promising therapeutic target. The high homology between human and canine CSPG4 and the recognized translational power of canine tumors as preclinical models for human malignancies prompted us to evaluate CSPG4 expression and the consequences of its immune-targeting for both human and canine OSA treatment. Methods: We analyzed CSPG4 overexpression in human and canine OSA samples and its significance for the survival of OSA patients. We exploited functional in vitro experiments to assess the antitumor potential of CSPG4 immune-targeting. Results: CSPG4 is overexpressed in OSA and has possible clinical implications as suggested by an evident correlation between CSPG4 overexpression and a shorter survival for both OSA-affected humans and dogs. The potential of CSPG4 immune-targeting for OSA treatment came from the ability of anti-CSPG4 monoclonal antibodies and sera, derived from human-CSPG4-DNA vaccinated canine patients, to significantly inhibit human and canine CSPG4-positive OSA cell proliferation, migration, and osteospheres generation. Moreover, CSPG4 immune-targeting has been shown to potentiate the effect of doxorubicin. Conclusions: Overall, these results provide the rationale to investigate the CSPG4 immune-targeting as a promising weapon for the treatment of CSPG4-positive OSA canine patients, to be successfully translated to a human setting.